Validation of a self-perceived media competence instrument for pre-service teachers / Validación de un instrumento de autopercepción de competencia mediática para docentes en formación. Issue 2 (3rd April 2019) - Mateus, Julio-César; Hernández-Breña, Wilson; Figueras-Maz, Mònica
Abstract: Key to guaranteeing the fundamental human rights of freedom of expression and information is the development of media competence, particularly in schools. Training teachers in the area of media competence is particularly important for developing these skills in the broader citizenry. In order to provide educators and educational policymakers with a useful diagnostic tool, we have designed a self-perception questionnaire. The questionnaire was applied to a sample of Peruvian education students ( N = 501). On the one hand, the results confirm the construct's coherence, validity and instrumental reliability. On the other hand, they allow us to propose a theoretically based update to the way in which this construct is interpreted and applied, confirming the multidimensionality of media competence. Finally, we use this empirical evidence to discuss the integral, transversal and ecological status of media competence.